1988
DOI: 10.1007/bf00345500
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DQ system and insulin-dependent diabetes mellitus in Japanese: does it contribute to the development of IDDM as it does in Caucasians?

Abstract: Fifty-six unrelated Japanese patients with insulin-dependent diabetes mellitus (IDDM) were HLA-typed, and restriction fragment length polymorphism (RFLP) analysis was performed after enzyme digestion with Bam HI and Taq I by using both DR and DQ probes. As previously reported, increased frequencies of Bw54, Cw1, DR4, and DRw53, which are in strong linkage disequilibrium in the Japanese population and make the characteristic Japanese haplotype, were confirmed. DQw4, a new allele of the DQ system recognized by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
1
1

Year Published

1989
1989
2002
2002

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 22 publications
4
50
1
1
Order By: Relevance
“…The results and the calculated relative risks are in close agreement with those reported previously from studies of Japanese patients and controls (23)(24)(25). Both DR4 (relative risk = 4.62; P = 0.003) and DR9 (relative risk = 2.22; P value, not significant) are increased in the patient group, whereas the frequencies of the antigens DR2 (relative risk = 0.29; P = 0.036) and DR5 (relative risk = 0.13; P = 0.017) are decreased.…”
supporting
confidence: 90%
“…The results and the calculated relative risks are in close agreement with those reported previously from studies of Japanese patients and controls (23)(24)(25). Both DR4 (relative risk = 4.62; P = 0.003) and DR9 (relative risk = 2.22; P value, not significant) are increased in the patient group, whereas the frequencies of the antigens DR2 (relative risk = 0.29; P = 0.036) and DR5 (relative risk = 0.13; P = 0.017) are decreased.…”
supporting
confidence: 90%
“…We found that only 32% of the IDDM patients possessed the four susceptibility molecules, all being DR3/4 heterozygotes or DR3/3 or DR4/4 homozygotes. The DQA contribution is probably different in non-Caucasoid populations, as suggested in Japanese (47) or in Black (48) subjects in whom a particular DQa,,3 heterodimer, coded either in cis or in trans position, seems to be involved in disease predisposition.…”
Section: Dqa Locusmentioning
confidence: 99%
“…Inter-ethnic group studies support the hypothesis of conformational structure influencing diabetogenicity of some HLA alleles or haplotypes. For instance, among the Japanese, the DQB1*0401 allele is usually found on DR4-DQA1*0301-DQB1*0401 haplotypes and is associated with diabetes risk [58]. The DQB1*0401 and DQB1*0402 alleles differ only by one amino acid.…”
Section: Mechanisms Of Diabetogenicity Of Hla Moleculesmentioning
confidence: 99%